Study the Preservation Methods of Vibrio fischeri to Toxicant Detecting Kit - Tran Thi Huyen, Nga (VNU Journal of Science: Earth and Environmental Sciences, 2017)
This study focused on comparing two preservation methods of Vibrio fischeri : liquid storage and freeze-dried storage to find out the optimal condition and formulation for kit production. The liquid preservation method is based on six formulas of nutritional supplements according to six formulas (Sacarose 12%; NaCl 5%; skimmed milk 10% and NaCl 4%; skimmed milk 10% and NaCl 5%; Glyxerol 10%; skimmed milk 10%), component for cell protection and cell stabilization (combined with alginate microcapsules), then stored for six months at the temperatures of -20ºC, -5ºC, 5ºC and 25ºC. The freeze-dryied method is based on three formulas, including skimmed milk 10%; skimmed milk 10% and NaCl 1%; Lactose 10%. The samples were then stored for a 6-month period at -20ºC, -5ºC and 5ºC. The results showed that the liquid preservation method with 10% skimmed milk (S1) combined with alginate microcapsules, luminous intensity after 6 months was stable and highest. The luminous intensity of S1 was 9.8x10 4 RLU /ml after 4 months.